Improvement of the activity of the anti-HIV-1 integrase aptamer T30175 by introducing a modified thymidine into the loops - Antonella Virgilio (Nature Portfolio, 2018)
Abstract In this paper, we report our investigations on analogues of the anti-human immunodeficiency virus type 1 (HIV-1) integrase (IN) aptamer T30175 in which the individual thymidines forming the loops were replaced by 5-hydroxymethyl-2′-deoxyuridine residues (H). Circular dichroism, nuclear magnetic resonance and gel electrophoresis investigations clearly indicated that all the modified aptamers preserve the ability to form the original 5′-5′ end-stacked head-to-head dimeric G-quadruplex structure, in which each G-quadruplex adopts a parallel arrangement and is characterized by three G-tetrads, three propeller loops and one bulge-loop. All the modified aptamers were tested in an IN inhibition LEDGF-independent assay. While the modified aptamers INTB-H13 and INTB-H17 showed IC50 values comparable with that of the parent aptamer (INTB-nat), analogues INTB-H2, INTB-H5 and, to a lesser extent, INTB-H9 showed a higher ability to inhibit the HIV IN than the unmodified aptamer. Molecular modelling studies evaluating the aptamer/HIV IN interaction highlighted the ability of the modified thymidines to establish several contacts with the target protein. All the data point to the importance of loops in the aptamer/target interaction and suggest that the site-specific replacement of loop residues with commercially available analogues can be considered a straightforward strategy to improve the biological activities of several G-quadruplex aptamers.